Finding the Right Blend: Interplay Between Structure and Sodium Ion Conductivity in the System Na5AlS4–Na4SiS4 - Harm, Sascha; Hatz, Anna-Katharina; Schneider, Christian; Hoefer, Carla; Hoch, Constantin; Lotsch, Bettina V. (Frontiers in Chemistry, 2020)
The rational design of high performance sodium solid electrolytes is one of the key challenges in modern battery research. In this work, we identify new sodium ion conductors in the substitution series Na5-xAl 1-xSixS4 (0 ≤ x ≤ 1), which are entirely based on earth-abundant elements. These compounds exhibit conductivities ranging from 1.64 · 10-7 S cm-1 for Na4SiS4 to 2.04 · 10-5 S cm-1 for Na8.5(AlS4)0.5(SiS4)1.5 (x = 0.75). We determined the crystal structures of the Na+ -ion conductors Na4SiS4 as well as hitherto unknown Na5AlS4 and Na9(AlS4)(SiS4). Na+-ion conduction pathways were calculated by bond valence energy landscape (BVEL) calculations for all new structures highlighting the influence of the local coordination symmetry of sodium ions on the energy landscape within this family. Our findings show that the interplay of charge carrier concentration and low site symmetry of sodium ions can enhance the conductivity by several orders of magnitude.